FRI0374 THE RISK OF INFECTION BY TUMOR NECROSIS FACTOR INHIBITORS AND ITS ASSOCIATED FACTORS IN PATIENTS WITH ANKYLOSING SPONDYLITIS: RESULT FROM KOREAN NATIONAL HEALTH INSURANCE DATA. (June 2019) - Koo, Bon San; Lim, Yu-Cheol; Lee, Min-Young; Jeon, Ja-Young; Yoo, Hyun-Jeong; Oh, In-Sun; Shin, Ju-Young; Lee, Eui-Kyung; Kim, Tae-Hwan
Abstract : Background: Tumor necrosis factor inhibitors (TNFi) are effective in patients who do not respond to non-steroidal anti-inflammatory drugs, or disease modifying anti-rheumatic drugs, and have been widely used in patients with ankylosing spondylitis (AS). However, there is some evidence that treatment with TNFi can increase the risk of infection in patients with AS. Objectives: The aim of this study was to investigate the risk of infection in patients with AS treated with TNFi. Methods: Data was obtained from insurance claims database of the Health Insurance Review & Assessment Service (HIRA) in South Korea. Patients who have been prescribed a TNFi such as etanercept (ETN), adalimumab (ADA), golimumab (GLM), and infliximab (IFX) to treat AS from 1 July 2012 to 30 June 2017 were enrolled. We evaluated the incidence rate (IR) and hazard ratio (HR) of serious infections including pneumonia, tuberculosis, and herpes zoster in each TNFi treatment group by using cox proportional hazard model. We further analyzed the HR of infection by sex. Results: A total of 2, 515 patients were included in the study, and they were prescribed ETN (n=528), ADA (n=914), GLM (n=628), or IFX (n=445). The IRs of serious infection were 1668.63, 1489.88, 1457.58, and 1399.16 per 1, 000 person years (pys) in ETN, ADA, GLM, and IFX treated groups, respectively. There was no significant difference in HR of serious infection between the TNFi groups. In the subgroup analysis of major infections, there was no difference in the HR of pneumonia between TNFi groups. However, the HR of tuberculosis with IFX group was significantly higher than that with ETN (adjusted HR 8.95, 95% CI: 1.12-71.4). In herpes zoster infection, there was no difference between TNFi groups in all patients, but the adjusted HRs significantly increased with GLM (adjusted HR 15.40, 95% CI: 1.64-144.34) and IFX (adjusted HR 10.02, 95% CI: 1.12-89.9) treatment as compared to ETN in female patients. Conclusion: Patients receiving IFX had a higher risk of contracting tuberculosis than those receiving ETN. Moreover, the risk of herpes zoster was higher in female patients treated with GLM and IFX than in those treated with ETN in Korea. References: [1] Kim JA, Yoon S, Kim LY, Kim DS. Towards Actualizing the Value Potential of Korea Health Insurance Review and Assessment (HIRA) Data as a Resource for Health Research: Strengths, Limitations, Applications, and Strategies for Optimal Use of HIRA Data. J Korean Med Sci2017;32:718-728. [2] Fouque-Aubert A, Jette-Paulin L, Combescure C, et al. Serious infections in patients with ankylosing spondylitis with and without TNF blockers: a systematic review and meta-analysis of randomised placebo-controlled trials. Ann Rheum Dis2010;69:1756-1761. Acknowledgement: Study sponsored by Pfizer Inc. Disclosure of Interests: Bon San Koo Grant/research support from: Pfizer, Yu-Cheol Lim: None declared, Min-Young Lee: None declared, Ja-Young Jeon Employee of: Pfizer, Hyun-Jeong Yoo Employee of: Pfizer, In-Sun Oh: None declared, Ju-Young Shin: None declared, Eui-Kyung Lee Grant/research support from: Pfizer, Tae-hwan Kim: None declared